2007
DOI: 10.1038/sj.mt.6300073
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Fluorescence Tracking of Dynamic Transgene Variegation in Stem Cells

Abstract: Transgene variegation is caused by epigenetic switching between expressing and silent states. gamma-retrovirus vectors can be variegated in stem cells, but the dynamics of epigenetic remodeling during transgene variegation are unknown. Here, we measured variegated enhanced green fluorescent protein gamma-retrovirus expression over 4 days in individual embryonic stem cells while tracking cells in order to create expression lineage trees: 56 colony founder cells and their progeny were tracked over seven generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 31 publications
(41 reference statements)
0
21
0
Order By: Relevance
“…We take an alternate approach, exploring the degree of variation within a clone, using single cell analysis facilitated by IRES-driven coexpression of intracellular fluorescent markers. Clones are normally assumed to be homogeneous but emerging fundamental research in bacteria [25][28], yeast [29][34], and more recently mammalian cells [35][39], has revealed that gene expression can vary significantly between genetically-identical cells, even in a common environment (reviewed in [40], [41]). We reasoned that this ‘hidden’ source of variation within clones [42], [43] might also have practical implications for cell line development, which are not yet widely appreciated.…”
Section: Introductionmentioning
confidence: 99%
“…We take an alternate approach, exploring the degree of variation within a clone, using single cell analysis facilitated by IRES-driven coexpression of intracellular fluorescent markers. Clones are normally assumed to be homogeneous but emerging fundamental research in bacteria [25][28], yeast [29][34], and more recently mammalian cells [35][39], has revealed that gene expression can vary significantly between genetically-identical cells, even in a common environment (reviewed in [40], [41]). We reasoned that this ‘hidden’ source of variation within clones [42], [43] might also have practical implications for cell line development, which are not yet widely appreciated.…”
Section: Introductionmentioning
confidence: 99%
“…1B). Previous studies have utilized the imaging chamber to restrict neurosphere growth to a two-dimensional monolayer and facilitate time course imaging and lineage informatics-based analysis (Ramunas et al, 2007). Although compression of an islet under the imaging chamber inevitably alters its structure, it was thought that cell-cell and cell-extracellular matrix connectivity and overall islet cell functions could be maintained by appropriate selection of both initial islet size and imaging chamber gap spacing.…”
Section: Resultsmentioning
confidence: 99%
“…The imaging chamber described herein has previously been implemented to study monolayer cultures (Karpowicz et al, 2005;Ramunas et al, 2007). Herein, chamber design criteria were investigated to ensure the imaging chamber could be used for collagen-embedded three dimensional cultures of human islets of Langerhans.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that this approach can also be generalized to other events that characterize the fate of sibling cells. A related but less analytical approach to correlate fluorescence expression between closely related cells, indicating synchronized epigenetic remodelling in embryonic stem cells, has been published recently (10).…”
Section: Symmetry Indices (Weighted Colless' Index C W )mentioning
confidence: 99%